Sistem Pemantauan Menggunakan Blynk dan Pengendalian Penyiraman Tanaman Jamur Dengan Metode Logika Fuzzy - Handi Handi; Hurriyatul Fitriyah; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Monitoring and watering have an important role in managing mushroom plants. However, the measurement used is the use of a thermometer as a manual and watering device. Through these fundamentals, it is conducting monitoring and automation of the fungal watering system with fuzzy logic method. The first process is to get information from the DHT11 sensor to send sensor data to the microcontroller for the process of output and humidity, the results of the data can be seen on the LCD screen. Blynk application is done as a remote monitoring. Fuzzy logic method was chosen to category the problem of input data to output data in conducting clean watering. From the sensor test the results obtained compared to the DHT11 reading sensor had an average error of 4.07%. In the process of watering the control system carried out as many as 10 times with a percentage error of 16.66%. Comparison of test duration has a difference of 45 seconds and the difference in water released by 500 ml. Although there are many more manual resections and long durations, the accuracy of the sensors and controllers with fuzzy logic method is more in line with the conditions needed in the mushroom place.